1995
DOI: 10.1007/bf01888366
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of tryptophan residues in α-neurotoxins fromOphiophagus hannah (king cobra) venom

Abstract: Two alpha-neurotoxins, Oh-4 and Oh-7, from the king cobra (Ophiophagus hannah) venom were subjected to Trp modification with 2-nitrophenylsulfenyl chloride (NPS-Cl). One major NPS derivative was isolated from the modified mixtures of Oh-4 and two from Oh-7 by HPLC. Amino acid analysis and sequence determination revealed that Trp-27 in Oh-4, and Trp-30 and Trp-26 and 30 in the two Oh-7 derivatives, were modified, respectively. Sulfenylation of Trp-27 in Oh-4 caused about 70% drop in lethal toxicity and nicotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The indole ring of this conserved tryptophan is exposed to the solvent. Modification of Trp 27 in a long neurotoxin analogue (Oh-4) from the king cobra venom showed a significant loss in the toxicity and acetylcholine binding efficiency of the toxin (37). Lys 24 is yet another residue that is well conserved among the neurotoxins (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The indole ring of this conserved tryptophan is exposed to the solvent. Modification of Trp 27 in a long neurotoxin analogue (Oh-4) from the king cobra venom showed a significant loss in the toxicity and acetylcholine binding efficiency of the toxin (37). Lys 24 is yet another residue that is well conserved among the neurotoxins (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a chemical modification study indicated the importance of tryptophan residue for toxicity of DNTx‐III (Figure B). Among the many amino acid residues in neurotoxins, tryptophan was found to be important for its function; modification of this residue resulted in the complete loss of its acetylcholine receptor‐binding activity and a decreased toxic effect . The chemically modified as well as unmodified DNTx‐III gave a single sharp band in Western blot (Figure D), suggesting that modified toxin is structurally intact.…”
Section: Discussionmentioning
confidence: 99%
“…Although several α-neurotoxins have been previously isolated from O. hannah venom to study their protein structure (Lin et al, 1995a;Lin et al, 1995b;Chang et al, 1995;Lin et al, 1997;Chang et al, 2000;Roy et al, 2010), there is a need for pharmacological studies to characterize the main neurotoxins that potentially contribute to human neuromuscular paralysis. This study aimed to isolate the main neurotoxins from O. hannah venom and identify the mode of action, as well as determine the in vitro efficacy of Thai Red Cross Society King Cobra antivenom in neutralizing them.…”
Section: Introductionmentioning
confidence: 99%